Q-switched Fiber Laser with Silver Nanoparticles-PVA in an Erbium-based Ring Configuration - Othman A.M, Miaikil; Arni Munira, Markom; Nurul Athirah, Mohamad Abdul Ghafar; Hazlihan, Haris; Abdul Razif, Muhammad; Sulaiman, Wadi Harun (INTI International University, 2024)
This study examines the fabrication and experimental setup of a Q-switched fiber laser using a silver nanoparticle-polyvinyl alcohol (AgNPs-PVA) thin film as a saturable absorber. The thin film was produced by combining 5 mg of silver nanoparticles with 50 mg of polyvinyl alcohol in ionized water, followed by molding and drying. The laser showed a clear peak at 1560 nm, indicating precise output adjustment, with a slope efficiency of 9.69%. Pump power ranged from 49.06 to 81.37 mW, resulting in output power between 4.27 and 7.4 mW and pulse energy increasing from 100 nJ to 136.68 nJ. An optical-signal-to-noise ratio (OSNR) of 75.16 dB and a stable RF spectrum demonstrated strong laser stability. This work's competitive performance, ease of fabrication, and promising results suggest that the AgNPs-PVA thin film is a viable candidate for Q-switched fiber lasers, advancing laser technology.